∫ 2 3 [ x 2 + x + 1 ] + [ x 2 + x + 1 ] − [ x 2 + x + 1 ] + [ x 2 + x + 1 ] − ⋯ d x
If the value of the integral above is V , input 1 0 V as the answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us first try to generalize a few things,
a + a − a + a − … = m a − a + a − a + … = n ⇒ { a + n = m a − m = n
Squaring both the equations,
a + n = m 2 a − m = n 2 m 2 − n 2 = m + n m − n = 1
Now placing m = a + n in and squaring,
a + n = n 2 + 2 n + 1 n 2 + n + 1 − a = 0 n = 2 − 1 + 1 − 4 ( 1 − a )
Similarly,
m = 2 1 + 1 − 4 ( 1 − a )
So, in our original question, a = x 2 + x + 1 and therefore,
n = 2 − 1 + 1 − 4 ( 1 − x 2 − x − 1 ) = 2 − 1 + 4 x 2 + 4 x + 1 = 2 2 x = x
Similarly,
m = x + 1
∫ 2 3 ( x + 1 ) d x = ( 2 x 2 + x ) ∣ 2 3 = 2 3 2 + 3 − 2 2 2 − 2 = 2 7
Let ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ u = x 2 + x + 1 + x 2 + x + 1 − x 2 + x + 1 + x 2 + x + 1 − ⋯ t = x 2 + x + 1 − x 2 + x + 1 + x 2 + x + 1 − x 2 + x + 1 + ⋯
⟹ { u 2 = x 2 + x + 1 + t t 2 = x 2 + x + 1 − u . . . ( 1 ) . . . ( 2 ) ⟹ ( 1 ) − ( 2 ) : u 2 − t 2 = t + u ⟹ ( u − t ) ( u + t ) = u + t ⟹ u − t = 1 ⟹ u = t + 1
⟹ ( 1 ) : ( t + 1 ) 2 = x 2 + x + 1 + t ⟹ t 2 + 2 t + 1 = x 2 + x + 1 + t ⟹ t 2 + t + 1 = x 2 + x + 1 ⟹ t = x ⟹ u = x + 1
Therefore, ∫ 2 3 u d x = ∫ 2 3 ( x + 1 ) d x = [ 2 x 2 + x ] 2 3 = 2 3 2 − 2 2 + 3 − 2 = 3 . 5 ⟹ 1 0 V = 1 0 × 3 . 5 = 3 5 .
Problem Loading...
Note Loading...
Set Loading...
x + 1 = ( x + 1 ) 2 = x 2 + x + 1 + x = x 2 + x + 1 + x 2 = x 2 + x + 1 + x 2 + x + 1 − ( x + 1 ) = x 2 + x + 1 + x 2 + x + 1 − ( x + 1 ) 2 And now the same pattern follows as that from the first step to generate the required pattern. Hence, ∫ 2 3 ( x + 1 ) d x = 2 1 ( x 2 + 2 x ) ∣ 2 3 = 2 7 ∴ 1 0 × 2 7 = 3 5